ANALISIS KUALITAS DAN KUANTITAS RNA TOTAL VARIETAS KACANG TUNGGAK (Vigna unguiculata L. Walp) ASAL KABUPATEN MALUKU BARAT DAYA - Karuwal, Ritha Lusian (Program Studi Pendidikan Biologi FKIP Unpatti, 2021)
Background: A preliminary study of total RNA isolation from young cowpea (Vigna unguiculata L. Walp) plant has been carried out. The results of total RNA isolation both qualitatively and quantitatively are a prerequisite for research related to gene expression. This study aims to analyze the quality and quantity of total RNA of cowpea leaves from Southwest Maluku district. Methods: The leaf samples used in this study were from eight varieties of cowpea plants at the age of four weeks after planting. Furthermore, RNA isolation used the Accuzol kit while the quality and quantity analysis was carried out by electrophoresis and spectrophotometry. Results: The results showed that the leaves from the sample collection for 4 weeks had good growth and were followed by total RNA isolation. Qualitatively, the results of the total RNA isolates electrophoresis had 1-3 bands in each variety, while quantitatively the total RNA isolates had absorbance values ​​ranging from 1.50 to 2.03 and total RNA concentrations ranging from 1398.2 to 9884.1 ng / µl. Conclusion: The quality and quantity of total RNA is very important in gene expression analysis